Ideological Construction In Digital News Media: Discourse Surrounding The 2024 Election - Pontoh, Sriwahyuni; Lantowa, Jafar; Dewantoro Afandi, Wisnu; Rahmat, Nurnadela (Al-Lisan: Jurnal Bahasa, 2024)
The role of the media in the 2024 election became a polemic in the community. One of the causes was the differing news of the election in the mass media based on the ideologies adopted by the media. This condition also tended for similar patterns to occur in the elections that would be held in 2024. Various surveys have emerged regarding strong candidates for the position of President of the Republic of Indonesia. This study used a critical discourse analysis research method to uncover the ideological discourse of the 2024 Election Vortex. The research data were digital news that contained a digital media ideological discourse related to the 2024 Election Vortex. The data were sourced from three digital news media with the highest trust index in Indonesia, according to the research results by the Reuters Institute Digital News Report (2023:132). These media were Kompas.com (69%), CNN.com (68%), and liputan6.com (64%). The concept of Critical Discourse applied in this study was Theo van Leeuwen's framework for analyzing actors and social actions. The results showed that the three digital dailies with the highest level of trust in Indonesia, kompas.com, cnnindonesia.com, and liputan6.com, exhibited mixed views on the four main issues in their reporting. These differences reflected different ideologies.